Rihanna’s savage x fenty lingerie : deceptive marketing for all body types? - Brooks, Bradley, (SAGE business cases., 2022)
A business partnership between pop star Rihanna and TechStyle to sell Savage X Fenty (or X Fenty) branded lingerie seemed like an ideal business start-up and sales started strong. Rihanna provided the company star power and the products were designed inclusively for all body types, sizes, and ethnicities. However, two years into the business venture consumers were complaining about the company’s membership opt-out requirement and about the lack of transparency in pricing on the website. Accusations of deceptive marketing threatened the company’s image.